Wadiah Savings Product Marketing Strategy to Increase Customers at Bank Syariah Indonesia KCP Batang Toru - Fitri Hotdiana H.; Zul Fahmi Napitupulu; Muhammad Lathief Ilhamy Nasution (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
In contemporary business, the problem of depositing capital in banking institutions with various systems is usually through a system of savings, current accounts, and deposits. The marketing strategy in selling the products used by the Indonesian Sharia Bank KCP Batang Toru, especially the wadiah savings product, is generally the same as the marketing strategy of other banks, except that the Sharia Bank KCP Batang Toru has its own value. The bank has an approach to customers, both religious and emotional approaches where customers see that Islamic banks are banking financial institutions whose operations and products are developed based on the Qur'an and Hadith. What is the marketing strategy for the products of Bank Syariah Indonesia KCP Batang Toru? What are the obstacles faced by Bank Syariah Indonesia KCP Batang Toru in marketing? How do customers increase their wadiah savings products at Bank Syariah Indonesia KCP Batang Toru? The aim is to find out how the marketing strategy of wadiah savings products at Bank Syariah Indonesia KCP Batang Toru. To find out what are the obstacles faced by the Indonesian Sharia Bank KCP Batang Toru in carrying out marketing strategies. To find out how to increase customers towards wadiah savings products at Bank Syariah Indonesia at KCP Batang Toru. The method used in this study is a descriptive qualitative method to describe or explain the state of the object of wadiah savings in the marketing strategy. Researchers can conclude that the sequence of strategies that have the most opportunity to get customers is to use the cross selling model, distribute brochures (manual or telemarketing) to existing and WIC customers, introduce wafiah savings products through the BSI mobile application.